Role of seed borne inoculum on karnal bunt infection risks - Sharma, Ramesh Chand; Sharma, Indu (Journal of Cereal Research, 2025)
Field studies on the role of seed borne inoculum of Karnal bunt (KB) and infection risks were carried out at Punjab Agricultural University, Ludhiana during 2003-04 to 2011-12 using the most susceptible wheat variety, WH 542. The potential of KB infected seeds in causing the disease in subsequent years was determined by planting seed of different KB intensities (0.0 -10%) at different sites. The KB continued to appear up to five years in three of the sites, though in traces in some of the seasons. Weather conditions played a significant role in the disease development. Nevertheless, the pattern of disease occurrence was often independent of different KB intensities due to lateral movement of infective propagules across the plots. Occurrence of infection may have depended more on wind direction, random movement and chance landing of sporidia. Another study conducted from 2005-06 to 2007- 08 showed that disease occurred up to 100 m from the primary inoculum centre. In third experiment the disease incidence was observed to be comparatively higher when the bunted grains were powdered and applied at the soil surface than when used as whole grains beneath the soil. Even a single powdered infected grain, was capable of causing considerable infection around 10 m radius. The fourth and fifth experiments (2006-07 to 2007-08), respectively, carried out to ascertain the viability of sporidia in relation to nutritional component and field exposure showed that sporidia maintained their viability, respectively, for 21, 18 and 9 days in January, February and March under field conditions and also on soil extract and leaf washing agar up to 4th sub-culturing indicating their potential to survive and travel long distances.